Overtone singing: Physics and metaphysics of harmonics in east and west - Van Tongeren, Mark -1968 (Amsterdam Fusica, 2004)
Singing harmonics --Listening to harmonics --Tuvan throat singing --Overtone singing in other traditional music --A history of overtone singing in the West --Body, mind and beyond --The great realm.